Knowledge, attitude and behavioural intention towards halal food product recall among Muslim consumers in the Klang Valley, Malaysia - Yop @ Ayob, Rosmawati (2018)
The basic needs and essential to consumers is food. Muslim consumers have the right to get halal food for their consumption in order to preserve their faith. Therefore, it is important for Muslim consumers to ensure that only halal food is supplied to them. Besides, Muslim consumers are very concerned about the halal or haram status of the food and drink they take every day. This is due to increased knowledge among Muslim consumers regarding the importance of halal food and beverages. For a Muslim, the aspect of halal food should start from ‘farm to fork’; meaning quality control must start from the slaughtering, handling, processing, transportation, storage of food until serving. The current way of life and the trend of Muslim consumers have led to increased demand for processed such as frozen food, canned food, organic food, bread products and dairy products that meet halal requirements. Halal means that the product meets the requirements set by Shariah law, it represents the hygiene, quality, safety and health symbol (Toyyib) when it is manufactured strictly under the Halal Assurance Management System (HAS). Malaysia’s halal food market had in recent time experienced several halal food products recall issues. Halal food product recalls were caused by cross-contamination of haram substances with halal food along the supply chain. Hence, halal food product recall from the market is aimed at ensuring that the food products that are withdrawn are not being bought and used by Muslim consumers. The success of halal food products recall programme relies on Muslim consumers’ knowledge, attitude and behavioural intention towards them. Unfortunately, Muslim consumers’ knowledge, attitude and behavioural intention towards halal food product recall are varied and unpredictable. Therefore, the main objective of this study was to determine the knowledge, attitude and behavioural intention towards halal food product recall among Muslim consumers in Klang Valley, Malaysia. The study adapted three variables namely attitude, subjective norm and perceived behavioural control from the Theory of Planned Behaviour (TPB) model and two additional factors namely socio-demographic profiles and Muslim consumers’ knowledge as factors that influence Muslim consumers’ behavioural intention towards halal food product recall. This study was a quantitative study where a total of 1,050 of Muslim consumers were selected as respondents through a simple random sampling procedure in Klang Valley. A face-to-face interview with the respondents using a structured questionnaire based on 7-point Likert scales were used to obtain feedback on halal food product recall. Descriptive analysis, cross-tabulation analysis, chi-square analysis, Spearman’s correlation analysis and multiple linear regression analysis were performed to analyse the collected data. From the descriptive analysis, socio-demographic profiles of Muslim consumers were summarized into percentage and frequencies. The results from descriptive analysis revealed that respondents have a good knowledge level on halal food product recall, have a favourable level of attitude on halal food product recall and have a high level of behavioural intention towards halal food product recall. The results of cross-tabulation and chi-square analyses showed the associations between selected socio-demographic profiles namely gender, marital status and religiosity with behavioural intentions. Spearman’s correlation coefficient revealed that there was a significant but weak correlation between knowledge and attitude. Multiple linear regression analysis has indicated that the six variables were significant and accepted. Attitude, subjective norms, perceived behavioural control, age, income and religiousity indicated positive relationship with behavioural intention towards halal food product recall. Nevertheless, knowledge, gender, residential area, race, education, marital status were not significant with behavioural intention towards halal food product recall among Muslim consumers in Klang Valley, Malaysia. The results of this study can contribute to a better understanding of Muslim consumers’ knowledge, attitude and behavioural intention towards halal food product recall. Furthermore, the result from this study will help food companies and government agencies to design appropriate programs regarding halal food product recall in Malaysia.